Data Mining Methods: K-Means Clustering Algorithms - Mohammad Annas; Siti Norida Wahab (International Institute for Advanced Science & Technology (IIAST), 2023)
A data warehouse is a straightforward definition of a database. Data mining technology can be used to process mountains of data in databases to uncover new, fascinating, and useful information.Clustering is an approach to data gathering. As one technique for grouping data into clusters or groups, the K-Means Clustering Algorithm algorithm divides the data into those that share the cluster's traits and those that don't. data into groups, and data into groups, so that data into groups, and data into groups, so that data has the same traits is grouped in the same cluster. Other clusters are formed from data and clusters with distinct properties. additional categories. The knowledge/information gathered in the groups or clusters is helpful to policy consumers in the decision-making process.mact of making decisions.